Legal Position of Selling - Buying Confisced Land in the Framework of Implementing the Public Housing Program - Arifia, Cikal; Rizkianti, Wardani (Universitas Islam Sultan Agung, 2025)
Utilization of confiscated land as a source of land for public housing development programs is a strategic solution in dealing with land limitations in urban and semi-urban areas. However, the legal status of confiscated land originating from the results of confiscation for criminal acts presents its own challenges in the process of buying and selling and land conversion. The urgency of this study is to analyze the legal position of confiscated land in the sale and purchase agreement and the mechanism of land conversion in the context of civil law and collaboration between ministries in the realization of the national housing program. The study utilizes a normative legal method with a statutory approach and case studies, examining the provisions of Law No. 5 of 1960, Law No. 2 of 2012, and their implementing regulations. The study findings show that the transfer of rights to confiscated land is only valid through an auction mechanism based on a court decision that has permanent legal force and is evidenced by auction minutes as an authentic deed. In addition, cooperation between agencies such as DJKN, ATR/BPN, and the Ministry of PUPR must be based on a valid agreement and carried out with the principles of legal certainty, accountability, and justice. The use of confiscated land for public housing needs to be equipped with clear administrative and regulatory mechanisms to prevent disputes and protect the rights of affected communities.